Pendampingan Pembuatan Website Desa Tetebatu Sebagai Sarana Layanan Desa - Al Amin, Khayatullah Al-Amin; Ahwan Ahmadi; Hotman Khairuman Wahyu Utama; Diah Ayu Ardianti; Yek Dandi; Aspani Sahid (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
In the current digital era, developments in information and communication technology have brought significant changes in various aspects of life, including in the government sector. Village government, as one of the smallest government units, is required to follow technological developments in order to improve the quality of services to the community. Digitalization services are an effective solution in responding to the challenges of the times, especially in Tetebatu Village which is still oriented towards conventional services. Creating a village website is one form of application of digital technology which plays an important role in speeding up the public service process, information transparency, and increasing community participation. Through the website, the village government can convey information quickly and on target, from activity announcements to online village programs. Therefore, creating a village website as a means of digitizing village services is expected to be a solution to increasing the efficiency of public services, strengthening information transparency, and opening wider access for the community in various aspects of life in the village. It is hoped that this initiative can be the first step towards a village that is more modern, competitive and ready to face the digital era